STUDY OF ELEKTRON TRANSPORT CHAIN OF MICROALGAE CHLORELLA AND SPIRULINA IN PRESENCE OF LEAD IN THE ENVIRONMENT (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Effects of different lead concentrations on induction of chlorophyll a fluorescence were studied in Chlorella and Spirulina. Beginning with concentration of 12.5 mL/L falling of parameters of induction curve was observed. The change of these parameters indicates decrease of activity of PS II. It is also shown, that Spirulina is steadier in presence of lead in the environment, than Chlorella.
Keywords: lead concentrations; Chlorella; Spirulina; chlorophyll a